Where now for the critique of the liberal peace?. (June 2015) - Richmond, Oliver P; Mac Ginty, Roger
This article seeks to take stock of the critique of the liberal peace and identify what it has and has not achieved. It also asks 'where do we go from here?' The article surveys an agenda for future research and can also be read as a rebuttal of some recent literature that has attempted to shut down the liberal peace debate. The article opens with a quick recap of the bases of the critique of the liberal peace. It then outlines the 'achievements' of the debate and examines the failings and oversights of the original critique. Questions are raised about the epistemology and terms of the debate, and of the ability of critical intellectual projects to break through the material power held by mainstream intellectual and policy actors. In its final substantive section, the article asks 'where next for the critique of the liberal peace?' We conclude by highlighting avenues of research that might be fruitfully explored.